MODEL PENGEMBANGAN INOVASI TEKNOLOGI DAN KELEMBAGAAN KEMITRAAN RANTAI PASOK GUNA MENINGKATKAN DAYA SAING UKM - Osmad Muthaher; Mohammad Assegaf (Jurnal Ekonomi dan Bisnis, 2014)
This study is intended to improve the competitiveness of SMEs are becoming increasingly important due to the demands of the most buyer Internaional SMEs in the supply chain . This study will discuss the most innovative technology and institutional innovation model of development of SMEs in the supply chain . Technological innovations in the form of intelectual capital development and use of information technology systems approach intensification and diversification of institutional development in the supply chain. The population in this study wasthe entire industry and SMEs in Semarang district of approximately 2,000 SMEs . The sampling frame of this study is that SMEs in the district and the city of Semarang , while respondents in this study are the owner or manager of SME . The amount of sample used in this study were 100 respondents ( SMEs ) . Sampling was purposive sampling method is directed to managers or owners of SMEs by considering sample selection on the formal SMEs . The approach used is descriptive analysis to determine the form of the development of technological innovation that uses a systems approach to supply chain enterprises and institutions adopted SMEs ,Research results show that the Intellectual Capital and Technological Innovation Information Technology significantly influence , while the influence of technology Invasion seignifikan to institutional partnership and competitiveness.Keywords : Intellectual Capital, Information Technology , Technology Innovation , institutional partnerships and Competitiveness